A Hierarchical Coding Strategy for Live Cell Imaging of Protein‐Specific Glycoform. Issue 37 (8th August 2018) - Li, Siqiao; Liu, Yiran; Liu, Lu; Feng, Yimei; Ding, Lin; Ju, Huangxian
Abstract: Live cell imaging of protein‐specific glycoforms holds great promise for revolutionizing the study of glycochemistry. The imaging protocols developed thus far build upon the paired interplay of probe units, thus limiting the number of monosaccharide identification channels. A hierarchical coding (HieCo) imaging strategy, with DNA coding and decoding of protein and monosaccharides executed in fidelity to the hierarchical order of target glycoprotein, is reported herein and features expandable monosaccharide identification channels. A proof‐of‐concept protocol has been developed for MUC1‐specific imaging of terminal sialic acid (Sia) and fucose (Fuc) on MCF‐7, T47D, MDA‐MB‐231, and PANC‐1 cells, revealing distinct monosaccharide patterns for four types of cells. The protocol also permits dynamic monitoring of changes in MUC1‐specific monosaccharide patterns associated with both the alteration of cellular physiological states and the occurrence of a biologically important process. Abstract : Using code : A hierarchical coding strategy has been developed for live cell imaging of protein‐specific glycoform, in which DNA codes and decodes each structural motif in fidelity to the hierarchical order of the target glycoprotein. The strategy features expandable monosaccharide identification channels and should allow for a more comprehensive understanding of protein glycosylation mechanisms and functions.